Assessment of Three-Dimensional Reconstruction in Percutaneous Nephrolithotomy for Complex Renal Calculi Treatment - Tan, Haotian; Xie, Yaqi; Zhang, Xuebao; Wang, Wenting; Yuan, Hejia; Lin, Chunhua (Frontiers in Surgery, 2021)
Introduction: Three-dimensional (3D) reconstruction is a novel imaging technique widely used to improve surgical operations. Some studies have identified its role in Urology for percutaneous nephrolithotomy (PCNL). Objective: To explore the potential benefits of 3D reconstruction technology in PCNL for complex renal calculi treatment. Methods: A retrospective study involving 56 patients with complex kidney stones who underwent PCNL was conducted between September 30, 2018, to September 30, 2019. Group A patients (72) underwent the 3D reconstruction technique before PCNL, while group B (67) did not. The operation time, the duration of the hospital stay, the puncture accuracy, the decrease in hemoglobin concentration, the stone clearance rate, and the postoperative complications were noted and compared between the two groups. Results: The initial stone clearance rates two weeks after PCNL were 81.9 % and 64.2% in groups A and B, respectively (P < 0.05). The first-time puncture success rates were 87.5% and 47.8 % in groups A and B, respectively (P < 0.05). Group A had a shorter operation time than group B (62 min versus 79 min, P < 0.05). Besides, the 3D reconstructive technique-assisted patients (91.7%) had no or mild complications, compared with (74.6%) group B patients. There was no significant difference in hemoglobin decline and hospital stay between the two groups. Conclusions: The 3D reconstruction technology is an effective adjunct to PCNL in the complex renal calculi treatment.